Analisis Tuning Parameter PID Menggunakan Algoritma Genetika pada Pengontrolan Kecepatan Motor DC - Aliansyah, Achmad Nur; nurhayati, Nurhayati; Jaya`, st Nawal; Pagiling, Luther; Alam, Wa Ode Siti Nur; Nur, Muhammad Nadzirin Anshari (Majalah Ilmiah Teknologi Elektro; Vol 21 No 2 (2022): (Juli - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2022.v21i02.P17, 2022)
Abstract — The DC motors often experiences rotational speed instability due to disturbance. To overcome this, PID control can be applied to stabilize the speed. PID control is a combination of proportional, integral, and derivative controls. To achieve good performance, it is necessary to tune these parameters using several methods, such as genetic algorithm. The genetic algorithm works by forming a population of individuals that potentially can produce optimal solutions judged by the fitness value. Several parameters are used in genetic algorithms such as population size, number of generations, crossover probability, and mutation probability. This study aims to analyze the genetic algorithm method for tuning PID control parameters in controlling the rotational speed of the DC motor. The results obtained genetic algorithm parameters with population size and the number of generations of 70, crossover probability of 0.9, mutation probability of 0.4 and a fitness value of 6.261e+18. PID parameters with value of Kp = 9.4429; Ki = 19.3255 and Kd = 0.45602 and system response with rise time value of 0.1212 s, settling time of 0.2562 s, overshoot of 0.0366% and steady-state error of 0.1739%. With these PID parameters, the DC motor can follow the setpoint at constant and changing load values.